Strategi Peningkatan Kualitas Website Bandiklat Prov Jatim Berdasarkan Kepuasan Pengguna Menggunakan Metode Webqual 4.0 - Sugiono, Nanang; Sunarto, Dewiyani; Eko W., Sri Hariani (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Abstrak: In a government agencies , websites be a pleasant important as a delivery of information , communication , and transactions between public administration. Government agencies in education and training (Bandiklat Prov Jatim) have a website www.bandiklat.jatimprov.go.id website that aims to provide information on the activities and institutional training to Government Employee. However , managers website Bandiklat Prov Jatim feel website built could not attract internet users to visit www.bandiklat.jatimprov.go.id .This needs to be an increase in on the quality of the website bandiklat prov east. The purpose of this research to analyze the links between the quality of website and user satisfaction.. Analysis the quality of website do with some stage, first the data collection and interview to the related. Then make and spreading the questionnaire.The analysis influence the quality of website use Multiple Linear Regression, among others test validity, realibilitas, test the assumption, and the the regression coefficient together and partial. The results of the analysis testing this indicates that variable the Usability Quality, and Information Quality have had a positive impact and significant impact on User Satisfaction while in Interaction Quality do not affect positive and significant impact on user satisfaction.